Evaluating Board Candidates: A Threat-Contingency Model of Shareholder Dissent Against Female Director Candidates - Mitra, Arjun; Post, Corinne; Sauerwald, Steve (Organization Science, 2021)
Given the growing corporate social responsibility (CSR) pressures to increase board gender diversity and the scrutiny afforded to firms that fail to appoint female directors, one may expect shareholders to vote with greater support for women (than for men) nominated to boards. However, diversity management research suggests that pressures to improve female representation in organizations and in leadership roles may also backfire. We propose a threat-contingency model of shareholder dissent against female director candidates to explain when shareholders will be more or less likely to dissent against female (relative to male) directors. Specifically, we advance CSR legitimacy threats and agency threats as conditions contextualizing shareholder dissent against female director candidates. Using a sample of 50,202 director elections at 1,104 public firms from 2003 to 2015, we find that female directors receive less dissent from shareholders; further, low female board representation intensifies this leniency as CSR legitimacy threats become more salient. However, when firm-related agency threats occur (e.g., firm underperformance and media controversies), shareholders’ leniency toward female director candidates dissipates, and when directors themselves present agency threats (e.g., director attendance problems and nonindependence), shareholders evaluate female directors more harshly than male directors. Underlining the relevance of our theory, our supplementary analyses show that shareholder dissent increases the probability of director turnover. These findings contribute to theory and research on women on boards, firm responses to institutional pressures, and shareholder dissent.